Blog-Based Self-Understanding to Increase Self-Efficacy of Vocational High School Students - Lacksana, Indra; Majdi, M Zuhdi Zainul; Mafirja, Sulma (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Self-efficacy has an important role related to students' self-understanding. Lack of student self-understanding can result in students committing crimes, so it is essential to recognize and understand the potential of the student's self. This study aims to produce an innovation related to the media in guidance and counseling using blog-based self-understanding media to improve student self-efficacy. This research uses the Borg and Gall method, which has been simplified into five stages by the Puslitjaknov Team, but this research is limited to small scale tests. Pre-experimental research design: one-group pretest-posttest design using purposive random sampling involving ten students. Research findings show that blog-based self-understanding is useful for increasing student self-efficacy.